2021
DOI: 10.31234/osf.io/9mutg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychosocial Characteristics of Involuntary Celibates (Incels): A Review of Empirical Research and Assessment of the Potential Implications of Research on Adult Virginity and Late Sexual Onset

Abstract: This narrative review provides a qualitative synthesis of more than 40 years of research on involuntary celibacy, late sexual onset, and adult virginity. Studies suggest that Incels struggle with a lack of sexual and romantic intimacy, and that their negative body image, shyness, poor social skills compounded by inexperience with sexual and romantic relationships contribute to further restrict their opportunities to build rapport with potential romantic or sexual partners. In line with life course theory, many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Our motivation for emphasizing these variables stems from various compelling factors. Regarding well-being, a comprehensive review of Stijelja's literature [2] revealed limited scientific research, apart from Speckhard and Ellenberg's [14] and Daly and Laskovtsov's [18] studies examining the potential for self-harm and suicide tendencies in incel posts, despite romantic relationships being a strong predictor of well-being [45]. Although research on incels is still in its infancy, some information about incels' well-being can be inferred from results indicating that romantic loneliness is associated with lower well-being and negative emotions [46], and romantic loneliness is higher among individuals who perceive themselves as involuntarily single rather than voluntarily single [47].…”
Section: Mental Well-being and Self-esteemmentioning
confidence: 99%
See 2 more Smart Citations
“…Our motivation for emphasizing these variables stems from various compelling factors. Regarding well-being, a comprehensive review of Stijelja's literature [2] revealed limited scientific research, apart from Speckhard and Ellenberg's [14] and Daly and Laskovtsov's [18] studies examining the potential for self-harm and suicide tendencies in incel posts, despite romantic relationships being a strong predictor of well-being [45]. Although research on incels is still in its infancy, some information about incels' well-being can be inferred from results indicating that romantic loneliness is associated with lower well-being and negative emotions [46], and romantic loneliness is higher among individuals who perceive themselves as involuntarily single rather than voluntarily single [47].…”
Section: Mental Well-being and Self-esteemmentioning
confidence: 99%
“…'Incel' is an abbreviation for "involuntary celibate," referring to a member of an online subculture mostly composed of heterosexual men who identify as involuntary celibate, unable to have romantic or sexual relationships not by choice but due to various reasons, often attributed to external factors or society. These individuals presuppose a natural entitlement to sex, attributing the unavailability of a romantic or sexual partner to not being attractive according to specific criteria independent of their will [2]. The incel community operates predominantly online, providing an outlet for expressing misogynistic hostility, frustration, and blaming society for a perceived failure to include them [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with these findings, Elliot Rodger reportedly struggled with suicidal ideations (Brugger 2015); Harper-Mercer and Minassian had been diagnosed with Asperger's syndrome (Anderson 2017;JCS 2021); and Davison claimed to have autism (Weaver and Morris 2021). Indeed, mental health is one of the most prevalent discussion topics on Incel forums (Stijelja 2021), yet, to date, there is little empirical research connecting Incel mental health and radicalization.…”
Section: Introductionmentioning
confidence: 99%